An Error Analysis of the Students’ Difficulties in Pronunciation Faced by the Second-Year Students of MAN 2 Bireuen (A Case Study) - Malahayati, Malahayati; Iswadi, Iswadi (Journal of English Education and Social Science, 2023)
The problem of this research is: what are the most dominant of pronunciation error words produced by students of MAN 2 Bireuen. The objective of this research is : to find out the most dominant of pronunciation error words produced by second years students of MAN 2 Bireuen. This research is categorized into a case study used descriptive qualitative method because this research was to find the dominant error words produced by students. The researcher conducted this research at MAN 2 Bireuen, the subject of the research is the second year students which consisted of 11 students. Furthermore, through error analysis of pronounciation in Malem Diwa text that’s given to second year students of MAN 2 Bireuen has been proven that students produced error when they read the text. The result of this study indicate that students dominant produced error words are noun with the average percentage 38,36% and students still face some factors; first they do not know about pronunciation, second they obtained difficulties in pronouncing new English words, the last is teachers’ neglect about pronunciation focus study during the learning process.